PENGARUH PEMANFAATAN SHORT MESSAGE SERVICE (SMS) TERHADAP KEPATUHAN KUNJUNGAN ANTENATAL CARE PADA IBU HAMIL DI RUMAH BERSALIN MITRA ANANDA PALEMBANG - Sari, Era Mardia; Rohmin, Anur; Hariani, Desi; Syafriani, Elvina Indah (NHM PRESS, 2023)
Abstract Pregnancy is one of the most essential phases for women. The average normal pregnancy will last for 40 weeks or approximately 275 days. The time of pregnancy is divided into 3 trimesters, where each trimester lasts for 3 months. The first trimester lasts 12 weeks, the second trimester lasts 15 weeks and the third trimester lasts 13 weeks. Pregnancy, childbirth, postpartum and newborns are physiological conditions that can turn into pathological conditions, so continuous and quality care is needed as well as carrying out regular prenatal checks during pregnancy. In implementing health efforts, mothers are family members who need to get priority. Efforts to improve maternal health receive special attention. It is important to monitor the health status and performance of maternal health efforts. This is because the maternal mortality rate is a sensitive indicator in describing the welfare of society in a country. This study aims to determine the effect of using Short Message Service (SMS) on adherence to antenatal care visits in pregnant women. This research is a quasi-experimental research in which there are interventions or treatments given to respondents. The sample in this study were 52 pregnant women who underwent pregnancy checks at the Mitra Ananda Maternity Hospital, which were divided into 2 treatment and control groups. The analysis was used to determine the effect of adherence to antenatal care visits in the intervention group and the control group using the Mc Nemar test. The results of the analysis show that the p value (0.001) is smaller than α (0.05) meaning that there is an effect of the use of SMS (Short Message Service) on compliance with antenatal care visits in pregnant women.